Effect of a lifestyle-integrated functional exercise (LiFE) group intervention (sLiFE) to falls prevention in non-institutionalized older adults. Protocol of a randomised clinical trial - Llamas-Ramos, Inés; Llamas-Ramos, Rocío; Lugones-Sánchez, Cristina; González-García, Susana; Tamayo-Morales, Olaya; Alvarado-Omenat, Jorge Juan; Pablos-Hernández, Carmen; Gómez-Marcos, Manuel A.; García-Ortiz, Luis; Rodríguez-Sánchez, Emiliano (Frontiers in Public Health, 2024)
Introduction: Personalized programs of integrated strength and balance activities have been shown their effectiveness in falls reduction in the elderly.Objective: To measure whether a group intervention with the strength and balance principles of the sLiFE program is more effective than standard health advice in reducing the incidence of falls.The study will comprise 650 participants with more than 65 years who live at home, observing established inclusion and exclusion criteria. Participants will be randomly assigned in two groups: group intervention (n=325) and standard health advice (n=325). The intervention group will follow the balance and strength activities described in the LiFE program manual. The group intervention will be carried out in groups of 12-14 and will consist of seven one-hour sessions over 12 weeks in health centres. Incidence of falls and quality of life will be assessed as primary outcome variables. Fear of falling and exercise adherence will be analysed as secondary outcome variables.Discussion: Physical activity has been put forward as an effective treatment technique for these patients; however, long-term adherence to these programs remains a challenge. Group interventions could reduce dropout rates.Falls represent a major health problem globally due to the disability they cause in older people. Prevention would help reduce not only their incidence but also the health costs derived from their treatment. Group intervention helps clinicians to save resources and time, being able to attend more people with the same quality of care.